Analysis of the Effective Tax Rate and Its Determinant Factors - Tufahati Ainia Mandavani; Einde Evana; Trijoko Prasetyo (International Journal of Economics Accounting and Management, 2025)
Tax avoidance remains a significant concern in Indonesia’s tax administration, particularly among publicly traded companies on the Indonesia Stock Exchange. This research explores the disparity in Effective Tax Rate (ETR) as an indicator of tax avoidance across various industry sectors and aims to determine the key factors driving these disparities. The study evaluates sectoral attributes such as financial complexity, transfer pricing mechanisms, capital structure, and deferred tax liabilities. Employing panel data regression on a dataset of 135 firms from eleven different sectors over a five-year timeframe, this study analyzes the influence of these variables on corporate tax avoidance. The results show that transfer pricing, capital structure, and deferred tax costs have a notable impact on ETR, suggesting their significance in shaping corporate tax strategies. Furthermore, the research indicates that patterns of tax avoidance vary across sectors, with industries such as mining, finance, and manufacturing displaying more pronounced avoidance practices. These findings underscore the tendency of firms to adopt tax planning approaches that align with the unique characteristics of their respective sectors. Ultimately, the study offers meaningful insights into corporate tax behavior and contributes to the formulation of more effective, sector-based tax compliance policies for regulators and decision-makers.